Preface (about the conference ICAAM2018) - Ashyralyev, Allaberen; Sadybekov, Makhmud A. (Bulletin of the Karaganda University. Mathematics Series, 2018)
This issue is a collection of 14 selected papers. These papers are presented at the Fourth International Conference on Analysis and Applied Mathematics (ICAAM 2018) organized by Near East University, Lefkosa (Nicosia), Mersin 10, Turkey. The meeting was held on September 6–9, 2018 in North Cyprus, Turkey.